1992
DOI: 10.1177/030802269205500307
|View full text |Cite
|
Sign up to set email alerts
|

How Do Clients Benefit from Snoezelen? An Exploratory Study

Abstract: An exploratory study involved observation of four clients of the Botleys Park Sensory/Snoezelen Environment (SSE) in both the SSE and the villa. The clients were not known to the observer and were selected at random. The aim of the study was to explore the hypothesis that a designed change in care will give rise to an observable change in the behaviour of the recipients of that care. The results indicated that there was an apparent difference in the behaviour of the four clients observed between the villa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 1 publication
0
37
0
Order By: Relevance
“…Historically, sensory rooms were first developed for patients with moderate to profound 3 cognitive impairments (Fisher, Murray and Bundy 1991), learning disabilities (Long and Haig 1992), dementia (Hope, Easby and Waterman 2004) and for young children with complex disabilities (Watling et al 2006). In the USA, New Zealand and Australia, sensory rooms have been implemented to reduce containment interventions, specifically seclusion and restraint, in psychiatric settings (Champagne & Sayer 2003 However, there remains a paucity of research studies that have evaluated the usefulness of sensory rooms in psychiatric settings; a literature review identified twelve published studies in the international literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Historically, sensory rooms were first developed for patients with moderate to profound 3 cognitive impairments (Fisher, Murray and Bundy 1991), learning disabilities (Long and Haig 1992), dementia (Hope, Easby and Waterman 2004) and for young children with complex disabilities (Watling et al 2006). In the USA, New Zealand and Australia, sensory rooms have been implemented to reduce containment interventions, specifically seclusion and restraint, in psychiatric settings (Champagne & Sayer 2003 However, there remains a paucity of research studies that have evaluated the usefulness of sensory rooms in psychiatric settings; a literature review identified twelve published studies in the international literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Snoezelen environments are thought to facilitate relaxation, provide enjoyment experience and inhibit behavioural changes [30,31]. The stimulation is believed to promote a sense of enjoyment and a relief from tension and pressure, with consequent improvement in general behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have varied in the measures that they have used to assess the effects of multi-sensory therapy sessions, but the benefits which have been reported include: positive changes in behaviour Long & Haig, 1992); improved task concentration (Ashby et al, 1995;Lindsay et al, 1997); an increase in a variety of skills such as awareness of self, social interaction behaviours, communication, exploration and manipulation of stimuli (Houghton et al, 1998); relaxation (Slevin & McClelland, 1999); and a reduction in stereotypic self-stimulatory behaviours and an increase in adaptive behaviours such as exploratory behaviour or initiating contact with others (Shapiro et al, 1997).…”
Section: Learning Disabilitiesmentioning
confidence: 99%